Case Report: 18F-FDG PET/CT and Laparoscopic Nephron Sparing Surgery in the Management of Bleeding From Renal Metastases of Choriocarcinoma - Du, Yuancheng; Zhang, Xueping; Sun, Shengyang; Sun, Meihong; Yang, Dongyu; Yu, Xinyuan; Li, Kehao; Ma, Jie; Li, Yongxiang; Ge, Jinming; Liu, Changqing; Qiao, Liang (Frontiers in Oncology, 2022)
Choriocarcinoma is a cancer that usually occurs in the uterus during pregnancy. Although choriocarcinoma with renal metastasis and spontaneous renal hemorrhage is very rare, it can occur. We describe a rare case of metastatic choriocarcinoma, wherein the patient presented with acute abdominal pain due to a subcapsular hematoma secondary to a bleeding renal metastasis. We performed a laparoscopic partial nephrectomy to remove the tumor and control the bleeding. A retrospective analysis of revealed that metastasis was detected on 18F-fluorodeoxyglucose PET/CT, but not on CT alone. To our knowledge, a case of choriocarcinoma with such symptoms and treatment has not been described in recent literature. Our case illustrates that acute bleeding from a renal metastasis can be effectively managed by laparoscopic partial nephrectomy. It also demonstrates the advantage 18F-FDG PET/CT may have in the evaluation of metastatic choriocarcinoma.